Slowing health spending growth and expanding coverage: A bipartisan solution - Joseph Antos (American Enterprise Institute (AEI), 2019)
A common theme leading up to the 2020 election is that the Affordable Care Act (ACA) should be repealed and replaced.
Keywords: A; 330; Affordable Care Act Obamacare; health reform; Medicare for All